Effects of flight delays for airline operating a hub-and-spoke system - Bjarki Jónsson 1991- (2019)
Flight delays are a growing problem worldwide, causing excessive costs for airlines. Delays that originate from previous flights and spread to successive flights later during the day are known as propagation delays. The main objective of this thesis is to advance the understanding of how delays can be prevented or reduced. Cost consequences of delays are also discussed. WOW air, a former small airline operating a single hub-and-spoke system, will be used as a case study in this thesis. Specific routes are analysed and the reliability of the on-time performance of these routes is evaluated in order to determine to which extent individual routes cause delays to the flight network. Since both flight times and turnaround times are stochastic, simulations were performed for a sequence of flight routes to evaluate whether there are combinations of flight routes that are likelier to cause propagated delays to the flight network. The thesis will discuss how adding slack into the flight schedule and between flights at the hub airport can increase on-time performance and reduce delays caused by connection passengers. The results show that flights from Frankfurt Airport often arrive late into Keflavík Airport, therefore causing propagated delays to flights to North America, because these flights often wait for connection passengers coming from Frankfurt. The results also indicate that when certain routes, that involve Frankfurt flights, are paired into a sequence the probability of propagated delays is over 50%. Seinkanir á flugi er sívaxandi vandamál á heimsvísu og er það gríðarlega kostnaðarsamt fyrir flugfélög. Seinkun á flugi sem hefur þau áhrif að næsta flug lendir einnig í seinkun, er skilgreint sem afleidd seinkun (e. propagation delay). Meginmarkmið þessarar ritgerðar er að auka skilning á því hvernig er hægt að koma í veg fyrir eða draga úr seinkunum á flugi. Þá verður einnig fjallað um þann kostnað sem fylgir seinkunum á flugi. Framkvæmd verður tilviksrannsókn þar sem WOW air, sem var lítið flugfélag og starfið ...